Saamentutkimus tänään (Volume 234.0) (Finnish Literature Society / SKS, 2011)
Saamentutkimus tänään is an introduction to the Sámi studies, i.e. the scientific study of the Sámi people. It gives many-faceted basic information of the Sámi people and presents up-to-date views of the disciplines related to the Sámi studies, e.g. history, archeology, genetics, linguistics, comparative religion, folkloristics, ethnology etc. It provides scientifically based knowledge of the Sámi during the prehistory and pre-Christianity, dealing with reindeer herding, handicraft, the Sámi languages, Sámi literature and art and civil right questions, including participation in the international movement of the indigenous people. All the authors are eminent experts of their scholarly fields, and all the articles have been revised by the Academic representatives of the Sámi themselves